Negative ion formation during scattering of H-atom from-Al (111) Thin Films: Using Perturbative method - Jassem, Hayfaa A. (University of Thi-Qar Journal of Science, 2019)
In this work, electron capture by H- projectiles in grazing scattering from Al(111) thin films [ with difference thickness, which can be taken as a discrete set of values corresponding to different amount of atomic plane within Al(111)],is studied theoretically using Perturbative method. The resonance charge transfer(RCT) on thin film appears to be quite different from that on a semi - infinite free- electron approximation metal, this distinction is related to the difference of the electron structure of thin- metal films and the semi-infinite metal. The size quantization in this metallicfilms allows through the variation of the film thickness. Some of the feature of RCT on thin films have already been discussed based on non Perturbative methods ( example CAM method) studied , so we treat the same systems using CAM method for comparison .